Menelaah Fungsi Cultural Mediator dalam Promosi Vaksin di Pedesaan - Yun Fitrahyati Laturrakhmi (Fakultas Ilmu Politik dan Ilmu Sosial, Universitas Brawijaya, 2018)
Various cultural construct inhibit the vaccine promotion in rural areas. The perspective of a midwife about vaccines which emphasize in the biomedical tradition, becomes difficult to accept by the community who have non-biomedical perspective. As a result, posyandu cadres are needed to mediate that two different perspectives. The aim of this study is to explore the communication complexity in the promotion of vaccines that focused on the function of cadres as cultural mediators. Through an instrumental case study design, this study was conducted on 20 posyandu cadres and 3 midwives in the Gendro area, Tutur District, Pasuruan Regency - East Java. Data collected through FGD, interview and observation. This study reveals that posyandu cadres perform their functions as cultural mediators, especially in facilitating a constructive relationships between midwives and the community by redefining various biomedical terms and explanations to be accepted by the public in non-biomedical perspective. However, in cultural mediator’s role cadres can’t able to fulfill the community empowerment function because of the low level of health literacy. This research has shown that the concept of cultural mediators is not only applicable in the communication context involving migrants.Keywords: cultural mediator, cadre, promotion, vaccine.